The Future of Hidden Christian Heritage as Hybrid: Kakure Kirishitan and the Death of the Last ‘Keeper of the Books’ - McClelland, Gwyn (Entangled Religions, 2024)
Scholars sometimes assume that the distance between the Hidden Christian so-called Kakure Kirishitan faith and Christianity in Japan has increased to make any reconciliation between the two inconceivable, but new research using a framework of ‘hybridity’ shows that this is not the case. This article is based on interviews conducted between 2020 and 2025 on the Gotō Islands, Nagasaki Prefecture, Japan. The author focuses on a rapprochement evident today between Hidden Christian social and cultural worlds and Roman Catholic cultural life, alongside an affinity of the varied groups of Kakure Kirishitan with Buddhist and Shinto practices and cultural life. This article re-considers the future of ‘Hidden Christian heritage’ in the light of the 2018 ratification of UNESCO World Heritage sites that tends to elide the Kakure Kirishitan voice. Hidden Christians are religious groups that formed after 1613 due to the ban on Christianity in Japan and continually evolved since that time.